2014
DOI: 10.1016/j.pain.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a combination of gabapentin and donepezil in an experimental pain model in healthy volunteers: Results of a randomized controlled trial

Abstract: This double-blind, placebo-controlled, 3-period cross-over, 4-treatment option, incomplete block study (ClinicalTrials.gov number NCT01485185), with an adaptive design for sample size re-estimation, was designed to evaluate gabapentin plus donepezil in an established experimental model of electrical hyperalgesia. Thirty healthy male subjects aged 18-55 years were randomized to receive gabapentin 900 mg or gabapentin 900 mg+donepezil 5mg for 2 of the 3 treatment periods, with 50% of subjects randomized to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…In part II, pregabalin showed positive effects on cold pressor (PDT and PTT), electrical single stimulus (PTT), CPM (PDT) and thermal heat pain in normal skin. Alpha‐2δ ligands have previously been shown to affect pain in human pain models; gabapentin showed positive effects on pain in an electrical hyperalgesia model in healthy subjects . Conversely, gabapentin failed to show effects on heat PDT in healthy subjects .…”
Section: Discussionmentioning
confidence: 99%
“…In part II, pregabalin showed positive effects on cold pressor (PDT and PTT), electrical single stimulus (PTT), CPM (PDT) and thermal heat pain in normal skin. Alpha‐2δ ligands have previously been shown to affect pain in human pain models; gabapentin showed positive effects on pain in an electrical hyperalgesia model in healthy subjects . Conversely, gabapentin failed to show effects on heat PDT in healthy subjects .…”
Section: Discussionmentioning
confidence: 99%
“…99,107 Area of allodynia was reduced. 108,109 Contrasting effects were also seen after sural nerve stimulation. 108,110 The continuous electrical stimulation model induces both central sensitisation and continuous C-fibre mediated pain.…”
Section: Effect On Inflammation and Postoperative Pain Modelsmentioning
confidence: 90%
“…108,109 Contrasting effects were also seen after sural nerve stimulation. 108,110 The continuous electrical stimulation model induces both central sensitisation and continuous C-fibre mediated pain. Gabapentin increased the current strength required to induce pain and reduced area of secondary hyperalgesia but did not influence pain detection threshold in area of hyperalgesia.…”
Section: Effect On Inflammation and Postoperative Pain Modelsmentioning
confidence: 90%
See 1 more Smart Citation
“…Somewhat surprisingly, it has proven difficult in patient populations to demonstrate consistently an antinociceptive action of gabapentinoids in tests of mechanical sensitivity, which is presumed to reflect an action at the spinal cord. In fact, there are very few randomized control trials that examined this question; some found an antiallodynic action of systemic GP, 1 , 5 , 6 whereas other studies did not. 26 Interestingly, in the latter study, the patients in whom pregabalin was effective (against pain of HIV neuropathy) were the most sensitive in a test of pin-prick hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%